2020
DOI: 10.3389/fenvs.2020.00138
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Additive Chemicals From Marine Plastic Debris to the Stomach Oil of Northern Fulmars

Abstract: For this study, the transfer of plastic additives to stomach oil of northern fulmars (Fulmarus glacialis) has been investigated. Procellariiform seabirds retain oily components of their prey in theirs stomach as a means to store energy. A marine litterderived microplastic reference mixture and separately a marine litter-derived polystyrene sample were added to stomach oils in an experiment. A total of 15 additives, including plasticizers, antioxidants, UV stabilizers, flame retardants, and preservatives, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 69 publications
0
33
0
Order By: Relevance
“…Plastics gradually break down to microscopically small particles, but these may pose an even more serious problem (Thompson et al 2004;Bergmann et al 2015). Leaching of toxic additives from ingested plastics to seabirds has been shown by Tanaka et al (2013Tanaka et al ( , 2015Tanaka et al ( , 2019Tanaka et al ( , 2020; Yamashita et al (2018); and Kühn et al (2020a). Microplastics can also adsorb and concentrate organic pollutants from the surrounding water, but experimental results and model predictions are not all in agreement concerning release of such chemicals into marine organisms or associated negative effects (Arthur et al 2009;Browne et al 2008Browne et al , 2013Endo et al 2005Endo et al , 2013Gouin et al 2011;Koelmans et al 2013aKoelmans et al ,b, 2014Koelmans et al , 2016Moore 2008;Teuten et al 2007Teuten et al , 2009Chua et al 2014;Rochman et al 2013Rochman et al , 2014aTanaka et al 2013;Thompson et al 2009;Van Cauwenberghe & Janssen 2014;Cole et al 2015;Watts et al 2015;CBD 2016;Beaman & Bergeron 2016;Peda et al 2016;Besseling et al 2017;Heindler et al 2017;Hermabessiere et al 2017;Ribeiro et al 2017).…”
Section: Info Boxmentioning
confidence: 99%
“…Plastics gradually break down to microscopically small particles, but these may pose an even more serious problem (Thompson et al 2004;Bergmann et al 2015). Leaching of toxic additives from ingested plastics to seabirds has been shown by Tanaka et al (2013Tanaka et al ( , 2015Tanaka et al ( , 2019Tanaka et al ( , 2020; Yamashita et al (2018); and Kühn et al (2020a). Microplastics can also adsorb and concentrate organic pollutants from the surrounding water, but experimental results and model predictions are not all in agreement concerning release of such chemicals into marine organisms or associated negative effects (Arthur et al 2009;Browne et al 2008Browne et al , 2013Endo et al 2005Endo et al , 2013Gouin et al 2011;Koelmans et al 2013aKoelmans et al ,b, 2014Koelmans et al , 2016Moore 2008;Teuten et al 2007Teuten et al , 2009Chua et al 2014;Rochman et al 2013Rochman et al , 2014aTanaka et al 2013;Thompson et al 2009;Van Cauwenberghe & Janssen 2014;Cole et al 2015;Watts et al 2015;CBD 2016;Beaman & Bergeron 2016;Peda et al 2016;Besseling et al 2017;Heindler et al 2017;Hermabessiere et al 2017;Ribeiro et al 2017).…”
Section: Info Boxmentioning
confidence: 99%
“…This may result in an overestimation of the amount leached from plastic. Kühn et al (2020) used natural contaminated stomach oil and indeed only found limited transfer for five and no transfer for the other ten chemicals studied. Only few studies relate experimental observations with the chemical and sorbent characteristics.…”
Section: Weight Of Evidence From In Vitro Studiesmentioning
confidence: 93%
“…Furthermore, besides exchange fluxes between MP and gut fluid, the fluxes from food should be assessed in order to assure that the role of ingested MP is not negligible as compared to the parallel exposure pathways. For instance, Kühn et al (2020) observed leaching of five chemicals from MP into stomach oil sampled from seabirds. However, the uptake of chemicals from normal food and the concentrations of background chemicals in the oil were not measured or modelled, nor were kinetic parameters estimated, precluding conclusions regarding the relevance of the vector effect under environmentally realistic conditions.…”
Section: Resemblance Of Natural Exposure Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations